THE EFFECT OF INTELLECTUAL CAPITAL, CAPITAL STRUCTURE, LIQUIDITY AND FIRM SIZE ON FINANCIAL PERFORMANCE WITH AN INDEPENDENT BOARD OF COMMISSIONERS AS MODERATION IN BANKING COMPANIES IN THE INDONESIAN STOCK EXCHANGE - hardianto hardianto; Eka Nurmala Sari; Widya Astuty (Jurnal Ekonomi, 2023)
This study aims to examine and analyze the independent board of commissioners in moderating the influence of Intellectual Capital, Capital Structure, Liquidity and Firm Size on Financial Performance in Banking Companies on the Indonesia Stock Exchange. This research is a causal associative research with a quantitative approach. The research population is banking companies on the Indonesia Stock Exchange in 2017-2021 with a total of 44 companies. Selection of the sample by purposive sampling method with a total sample of 26 companies. The data source comes from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The type of research data is secondary data with data collection techniques with documentation and literature study. The data analysis technique used multiple linear regression analysis with the SPSS version 25 application. The results showed that Intellectual Capital and Firm Size have effect on Financial Performance. Capital Structure has an effect on Financial Performance. Liquidity has no effect on Financial Performance. The independent board of commissioners cannot moderate the influence of Intellectual Capital, Capital Structure, Liquidity and Firm Size on Financial Performance.